Influence-for-hire: Southeast Asia's shadow economy? - Tan, Sean (2022)
Influence-for-hire operations are spreading in the region while commercial agents are taking on an ever more prominent role both domestically and internationally. They not only help to obscure clients’ motives but also make such operations more accessible to an even broader set of threat actors.